Sensitivity and persistency of low-frequency component of heart rate variability: their use in clinical practice - A. R. Kiselev; V. I. Gridnev; O. M. Kolizhirina; V. F. Kirichuk (Российский кардиологический журнал, 2004)
In volunteers of various age and with varying myocardial contractility, parameters of heart rate variability (HRV) were assessed during functional test with controlled breathing (frequency control) and bicycle stress test. HRV spectral components had different sensitivity to periodical breathing of varying frequencies, with maximal reaction to ft 1 Hz diapason and 10-second breathing period. Sensitivity level correlated with heart pathology's severity. During exercise test, density persistency of 0.1 Hz component capacity depended on myocardial contractility. Sensitivity and consistency parameters of generated 0.1 Hz component can be used in assessment of heart disease severity.